Surviving the storm: manual vs. mechanical chest compressions onboard a lifeboat during bad weather conditions - Venema, Allart M.; Sahinovic, Marko M.; Absalom, Anthony R.; Wietasch, J. K. Götz (Frontiers in Disaster and Emergency Medicine, 2023)
Objective It is challenging for rescuers to perform cardiopulmonary resuscitation (CPR) onboard lifeboats, particularly during rough weather. A mechanical chest compression device (MCD) may provide better quality chest compressions. The aim of this study was to compare the quality of chest compressions performed by lifeboat-crewmembers with those of a MCD during rough-sea conditions. Methods Lifeboat-crewmembers were scheduled to provide compression-only CPR on a resuscitation-mannequin during two sets of five 6-minute epochs on a lifeboat at sea in two different weather-conditions. Simultaneously a MCD was used for compression-only CPR on another mannequin onboard the lifeboat. On a third occasion compressions by MCD only were measured due to COVID-19 restrictions. The primary outcome variable was the quality of chest compression, evaluated using published variables and standards (mean compression depth and compression frequency, percentage correct compression depth, percentage of not leaning on the thorax, percentage of correct hand placement on the thorax, hands-off-time). Results Six male lifeboat-crewmembers (mean age 35 years) performed CPR during two different weather conditions. In weather-conditions one (wind approximately 6-7 Beaufort/wave-height: 100-150 cm) quality of manual compressions was significantly worse than mechanical compressions for mean compression depth (p<0.05) and compression frequency (p<0.05), percentage correct compression depth (p<0.05), percentage of not leaning on the thorax (p<0.05), and hands off time (p<0.05). Crewmembers could only perform CPR for a limited time-period (sea-conditions/seasickness) and after one set of five epochs measurements were halted. In weather-condition two (wind approximately 9 Beaufort/wave-height approximately 200cm) similar results were found during two epochs, after which measurements were halted (sea-conditions/seasickness). In weather-condition three (wind approximately 7 Beaufort/wave-height approximately 300-400 cm) MCD compressions were according to resuscitation-guidelines except for three epochs during which the MCD was displaced. Conclusion Crewmembers were only able to perform chest-compressions for a limited time because of the weather-conditions. The MCD was able to provide good quality chest compressions during all but three epochs during the study period. More research is needed to determine whether MCD-use in real-life circumstances improves outcome. Inclusion of data on use of a MCD on lifeboats should be considered in future revisions of the USFD and resuscitation guidelines.